Study of the Isolation Effect of a New Damping Material for Environmental Vibrations Due to High-Speed Train Operation - Xiangqiu Wang; Xuguang Liu; Guoping Lei; Huojun Zhang (Advances in Civil Engineering)
In order to effectively reduce the environmental vibration hazards of high-speed railways, a new viscous damping material for vibration isolation is proposed in this paper. The damping effect of a trench filled with this material was verified by scaled model tests. On this basis, the Jinshazhou section of Beijing–Guangzhou high-speed railway was taken as the research object, and a three-dimensional finite element model was established including a high-speed railway, subgrade foundation soils, a vibration isolation trench, and a peripheral building. Combined with in situ measurements of environmental vibration of the studied railway section, the vibration isolation effects of both open and infill trenches were compared. The results show that the attenuation rates of the trench filled with the proposed material for the vertical and horizontal vibration acceleration level can be up to 14.0% and 13.2%, respectively, while the attenuation rates of the open trench are 11.1% and 11.9%, respectively. The vibration isolation trench filled with the new viscous damping material has a great damping effect on the vertical vibration across all frequency ranges, while a better isolation effect is observed for horizontal vibration when the frequency is less than 30 Hz or more than 50 Hz.